The value of c from the given expression is -
<h3>Function and values</h3>
Given the following function
c(n)= −c(n−1)+1
Given the following parameters
c(1)=3
Substitute
3 = −c(3−1)+1
3 = -2c + 1
-2c = 3-1
-2c = 2
c = -1
Hence the value of c from the given expression is -1
Learn more on equation here: brainly.com/question/2972832
#SPJ1
8.75-4.85= 3.90= cost of 6 bananas
3.9/6=0.65= cost of one banana
.65*4=2.60= cost of 4 bananas
4.85-2.60= 2.25= cost of 3 apples
2.25/3=.75= cost of an apple
Answer:
3rd option
Step-by-step explanation:
-5 is smaller than -2.
-2 is smaller than 1
1 is smaller than 3
Answer:
28x^2+3x-18
Step-by-step explanation:
Formula: (a+b)(a+b) = a^2 + a*b + a*b + b*b
Following this: 28x^2 -21x +24x -18
Then you combine like terms: 28^2 +3x-18
hope this helped!! :)
Answer:
(7x−2y)(a−b)
Step-by-step explanation: